Reformulation Of Mineral And Coal Mining Legal Policy Towards Strengthening The Principles Of Sustainability And Ecological Justice In Support Of The National Energy Transition - Rahardjo, Anthony; Budianto, Azis (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
Mineral and coal mining (Minerba) is a strategic sector in the Indonesian economy, but its management practices continue to raise serious issues related to environmental damage and ecological injustice. In the context of the national energy transition towards cleaner and more sustainable energy use, existing mining legal policies are deemed not fully adaptive to the need for environmental protection and the rights of affected communities. This study aims to analyze the current legal regulations for mineral and coal mining, identify their weaknesses, and formulate a direction for legal reform that can integrate the principles of sustainability and ecological justice. Using a normative juridical approach, this study looks at several relevant laws, such as Law Number 32 of 2009 concerning Environmental Protection and Management, Law Number 3 of 2020, and Law Number 6 of 2023 about Job Creation. The results indicate an imbalance between the interests of resource exploitation and environmental protection, as well as weak recognition of the rights of local and indigenous communities. Reformulation of mining legal policies needs to be directed at strengthening sustainable development principles, enforcing ecological obligations for mining businesses, and providing regulatory support for energy diversification. These efforts must be accompanied by increased oversight and law enforcement capacity to effectively and sustainably achieve the goals of the energy transition and ecological justice.